An Artiture of Formerly Incarcerated Tongan Students in Community College - Petelo, Steven (Art/Research International, 2024)
This article is taken from my dissertation study that explored the lived experiences of three Tongan Americans, each of whom were incarcerated in juvenile hall and are now attending college as a part of a transition program into local community colleges. The study introduced a Tongan version of the school-prison nexus by highlighting the ways in which the education and the justice systems work to ignore the dual culture realities of Tongans living in the United States. Adopting and fusing Fa‘avae’s (2016) talanoa and Lawrence-Lightfoot and Davis’ (1997) portraiture methodologies, I co-created a new approach Artiture—in collaboration with Taniela Petelo, my cousin, a Tongan-based international artist—to explore the following question: What are the challenges Tongan students face when they attend college after being incarcerated in the juvenile justice system? Findings from this Artiture highlighted intersections of family, history, cultural obligations and expectations, and the impact on Tongan Americans who deal with what Vakalahi (2009) calls “dual culture” (pg. 1259).